Analysis of Tomato Post‐Harvest Properties: Fruit Color, Shelf Life, and Fungal Susceptibility. Issue 2 (20th April 2020) - Thole, Vera; Vain, Philippe; Yang, Ray‐Yu; Almeida Barros da Silva, Juliana; Enfissi, Eugenia M. A.; Nogueira, Marilise; Price, Elliott J.; Alseekh, Saleh; Fernie, Alisdair R.; Fraser, Paul D.; Hanson, Peter; Martin, Cathie
Abstract: A wide variety of fresh market and processing tomatoes ( Solanum lycopersicum ) is grown and consumed worldwide. Post‐harvest losses are a major contributing factor to losses in crop productivity and can account for up to 50% of the harvest. To select and breed elite tomato varieties, it is important to characterize fruit quality and evaluate the post‐harvest properties of tomato fruits. This includes the analysis of shelf life (the period during which a fruit remains suitable for consumption without qualitative deterioration), color, and pathogen susceptibility. Tomato shelf life depends upon the rate of fruit softening which accompanies fruit ripening and exacerbates damage during transport and handling. Furthermore, the susceptibility of tomatoes to fruit pathogens is also often linked to fruit ripening, especially for necrotrophic fungi such as Botrytis cinerea, also known as gray mold. The methods described here are critical for determining fruit quality and fungal susceptibility during storage. © 2020 The Authors. Basic Protocol 1 : Fruit color as a determinant of fruit quality Basic Protocol 2 : Shelf life test of tomato fruits Basic Protocol 3 : Botrytis cinerea pathogen test of tomato fruits Support Protocol : Preparation of Botrytis spore inoculum